GAYA BAHASA DALAM KHOTBAH PENDETA DI GEREJA HKBP RAJAWALI PEKANBARU - Adelina, Maya Asti; Sinaga, Mangatur; Hermandra, Hermandra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study titled "Language Style" in Pastor's Homily at HKBP Church Rajawali Pekanbaru. The problem in this research is what the type of language are pastors in the church HKBP Rajawali pekanbaru in the sermon. This study aims to describe the style of the pastor in the sermon in the HKBP Rajawali Pekanbaru Church. This research is theoretically and practically useful to the readers. The theory used in this study is the theory of Tarigan (2013: 7) and Keraf (2010: 115). The time of this study started in December 2017 until June 2018. This type of research is qualitative research. The research method is qualitatively descriptive. The data source of this research is preacher preaching at HKBP Rajawali Pekanbaru Church. The study was conducted for two months, and in two months, eight weeks of weekly data retrieval took place by recording a pastor's sermon. Pastors in Pekanbaru include Rajawali HKBP's Pastor Toho Sinaga, sth and Pastor Riris br Sitorus. The data is collected by recording technology. Techniques of Data Analysis Research is descriptive analysis, data presentation and withdrawal of the final conclusion. Based on the results of the study the language style asidenton found, style polisidenton, style tautology, style metaphorical language, the language style climax, stylistic disillusionment, style koreksio, language artaussage of rhetorical speech style redundancy, stylistic parallelism, style simile, style kiasmic language and elliptical form.Key Words: Linguistic style, reverend sermon, HKBP Rajawali Pekanbaru